Deskripsi Pola Asuh Orang Tua Yang Menyebabkan Temper Tantrum Di Taman Kanak-Kanak Pembina Kota Pekanbaru - Pratiwi Gasril; Yeni Yarnita (Universitas Batanghari Jambi, 2021)
Kids’ future and development will really depend on the experience they obtained, included education and various parenting patterns consisting of democratic parenting, permissive parenting, and authoritarian parenting. The purpose of this research is to find out the description of parenting pattern which causes temper tantrum at Pembina Kindegarten Pekanbaru City. The method of this research was descriptive study to find out the description of parenting pattern which causes temper tantrum in pre school age with total samples were 109 respondents. The research results show that democratic parenting is 41 (37,6%), permissive parenting is 63 (57,8%), while authoritarian parenting is 5 (4,6%) and the result of temper tantrum obtains heavy temper tantrum in the amount of 2 children (1,8%), medium temper tantrum in the amount of 33 people (30,3%), and light temper tantrum in the amount of 74 people (67,9%). These results show that the majority of parenting pattern at Pembina Kindegarten Pekanbaru City is permissive and the majority occurance is light temper tantrum.